Numerical investigation of transient liquid nitrogen cavitating flows with special emphasis on force evolution and entropy features. (January 2021) - Liu, Yaoyao; Li, Xiaojun; Ge, Minghe; Li, Linmin; Zhu, Zuchao
Highlights: The impacts of free-stream temperature on the cavitation thermal effect are analyzed. The influences of free-stream temperature on each item of EPR are discussed quantitatively. The interactions between entropy features, vorticity and force coefficients are analyzed in detail. Abstract: This study aims to investigate the impacts of thermal effect on cavitation, entropy features and interactions among vorticity, force coefficients and entropy production rate (EPR) in a liquid nitrogen cavitating flow. Numerical results demonstrate that the increase in free-stream temperature intensifies thermal effect and weakens cavitation intensity. The EPR by fluctuating velocity gradient ( S ̇ D ' ' ' ' ) dominates the evolution of EPR, and the cavity shedding or collapse increases the velocity gradient, thereby increasing S ̇ D ' ' ' ' . The variation trend of EPR by wall region ( S ̇ W ) is consistent with S ̇ D ' ' ' ' . By contrast, EPR by temperature gradient ( S ̇ C ' ' ' ', S ̇ C ¯ ' ' ' ) always distributes on the liquid–vapour interface and increases with the development of the attached sheet cavity. Higher temperature acts as a disincentive to each item of EPR. The stable development of negative sheet vorticity at the leading edge increases the force coefficients nearly linearly. The counter clockwise vortex forms at the hydrofoil tail because the small-scale cloud cavity decreases the lift coefficient sharply. As the instability of attached sheet cavity is enhanced by re-entrant jet, the large vortex is dispersed into several clockwise vortexes, and positive vorticity occurs inside the cavity. Consequently, the force coefficients present a downward trend overall with intensive fluctuation. The distribution of EPR is similar to that of vorticity, and the opposite trend of entropy production integral and lift coefficient illustrates that the force can be used as a representation of energy loss to a certain extent.